Effect of α-tocopherol on the physicochemical, antioxidant and antibacterial properties of levofloxacin loaded hybrid lipid nanocarriers. (24th December 2020) - Islan, Germán A.; Gonçalves, Lídia M. D.; Marto, Joana; Duarte, Aida; Alvarez, Vera A.; Castro, Guillermo R.; Almeida, António J.
Abstract : Non-toxic hybrid lipidic nanoparticles become a promising tool for enhanced lung delivery of levofloxacin in combination with antioxidant properties. Abstract : In the global context of emerging pathogens associated with respiratory diseases, novel nanostructured lipid carriers (NLCs) having both antioxidant and antimicrobial properties produced by α-tocopherol (αT) and levofloxacin (LV), respectively, were developed. The hybrid NLCs were made of solid lipid esters and liquid αT as the central core, plus chitosan (Chi) and poloxamer 188 as surface stabilizers. Three formulations were rationally designed considering lipids with different physicochemical properties: cetyl ester (SS), glyceryl dibehenate (CO) and glyceryl tristearate (DY). The properties and stability of the nanoformulations were studied by dynamic light scattering considering the effects of the homogenization time, surfactant concentration, and initial lipid amount on the mean size, polydispersity index (PDI) and zeta potential of the nanoparticles. The effect of αT on the nanostructuration of the lipid matrix was demonstrated by X-ray diffraction, differential scanning calorimetry, and thermogravimetry analysis. The potential ability of the NLCs to interact with the mucosa was studied by rheological methods, demonstrating a reduction in mucin cohesiveness and elasticity due to the mucoadhesive properties of NLCs coated with chitosan. Solid lipid nanoparticles (SLNs) of SS, CO and DY encapsulated 58.0 ± 3.2, 25.7 ± 7.1, and 27.9 ± 1.5% LV, respectively, while the NLC formulations were able to encapsulate 80–90% LV and allowed controlled release of the drug. The enhanced antimicrobial properties of the SLNs/NLCs against Pseudomonas aeruginosa and Staphylococcus aureus were confirmed. The presence of αT in the formulations provided the antioxidant properties of the NLCs. Finally, no acute toxicities of the formulations were observed in two human lung cell lines (A549 and Calu-3).